The Effects of Unemployment Assistance on Unemployment Exits - Tomi Kyyrä (Institute of Labor Economics (IZA), 2021)
Many countries have a two-tiered unemployment compensation system which provides earnings-related unemployment insurance for a limited period of time and less generous unemployment assistance thereafter. This study evaluates the effects of a reform in Finland that increased the level of unemployment assistance by 22%. The reform led to a drop of 9% in the unemployment exit hazard, which can be attributed to fewer exits to both employment and inactivity. The implied elasticities suggest that a 10% increase in unemployment assistance reduces the unemployment exit hazard by 4% and the job finding hazard by 6%. These effects are relatively small compared to the existing evidence on the effects of unemployment insurance benefits.
Keywords: J64; J68; 330; unemployment assistance; labor market subsidy; hazard rate; unemployment duration